An Analysis of The Effect of Teaching Methods on Students’ Motivation in Learning English - Ricman, Oscar; Baka, Charlie; Sudarsi, Elim Trika; Ibrahim, Ilmiah; Faniriana, Maminiaina Andosoa (Institut Agama Islam Negeri Palopo, 2024)
This research aims to determine the effect of learning methods on students' learning motivation in English at SMP Kristen Makale. The method used was quantitative with a population of 127 class VII students and a sample of 40 students (32%), selected using proportional random sampling. Data was collected through observation, questionnaires and documentation, and then analyzed using simple linear regression and descriptive statistics. The research results show that learning methods have an influence of 53.1% on student learning motivation, with a correlation value (R) of 0.729. Lecture, demonstration, discussion, question and answer, and presentation methods all show high levels of student motivation, with percentages ranging from 72% to 76.8%. In conclusion, the learning methods used influence students' learning motivation, although some students are still not motivated. Teachers need to develop more diverse and innovative teaching methods to increase overall learning motivation. Keywords: English language, Teaching Methods and Learning Motivation